ANALISIS MANAJEMEN RISIKO TEKNOLOGI INFORMASI PADA WEBSITE UMKM XYZ BERDASARKAN FRAMEWORK ISO 31000: ANALYSIS OF INFORMATION TECHNOLOGY RISK MANAGEMENT ON UMKM XYZ WEBSITE BASED ON ISO 31000 FRAMEWORK - Galeh Pamungkas; Muhammad Bagas Tri Atmojo (UPPM Akademi Komunitas Semen Indonesia, 2021)
In the Era of Industrial Revolution 4.0 the main drivers of economic growth in Indonesia are Micro, Small and Medium Enterprises (MSMEs). According to data from the Ministry of Cooperatives, Small and Medium Enterprises in 2018, the number of MSMEs is 64.2 million or 99.99% of the number of businesses in Indonesia. The absorption of MSMEs is as much as 117 million workers or 97% of the absorbency of the business world workforce. Meanwhile, the contribution of MSMEs to the national economy (GDP) amounted to 61.1%, and the remaining 38.9% was contributed by large businesses amounting to only 5,550 or 0.01% of the number of businesses. But in the midst of the growth of MSMEs that have the potential of economic growth in Indonesia is increasing rapidly does not mean that rapid growth is free from problems. Various problems will certainly come to an end. The way to overcome the various problems that msmes will face is to overcome the risks that may occur and arise in the future. The method used in risk management is to use the STANDARD ISO 31000 method.